A Comparison of Serum Omega - 3 Fatty Acid Concentrations Between Patients with Coronary Heart Disease and Healthy Subjects - Alshatwi, Ali A.; Alrefai, Noura A. (Pakistan Journal of Nutrition, 2006)
Blood levels of eicosapentaenoic (EPA) and docosahexaenoic acids (DHA) are independently associated with elevated risk of death from coronary heart disease (CHD). The aim of this study was to compare the serum omega 3 and omega 6 fatty acid levels between patients with CHD and control subjects. The mean serum levels of triglyceride (TG) total cholesterol (TC) and low density lipoprotein cholesterol (LDLC) were higher in patients as compared with health subjects. The mean serum levels of alpha-linolenic acid (ALA), EPA, and DHA were significantly lower in the patients than in the control subjects. The mean serum concentrations of the ALA, EPA and DHA in patients were 3.04±0.75, 3.33±2.04, and 6.50±1.79 μg/dL, meanwhile the mean serum concentrations of the ALA, EPA and DHA in healthy subjects were 3.43± 0.50, 4.19±1.79, and 9.78±2.47 μg/dL. In contrast, the mean serum level of arachidonic acid (AA) was higher in the patients as compared with control subjects. The mean serum concentration of AA in patients and healthy subjects was 7.58±1.09 and 6.80±1.31 μg/dL, respectively. The ratio of serum omega-3/omega-6 fatty acids (FAs) was significantly lower in the patients than in the control subjects. In conclusion, the patients with CHD had low concentrations of Omega-3 FAs as compared with health subjects. In contrast, the level of AA is high as compared with healthy subjects. These data suggest that it is important to maintain omega-3 fatty acids level in serum of subjects, especially who are at risk of CHD for the purpose of preventing CHD.